Pengaruh Penyuluhan Modifikasi Video Terhadap Tingkat Pengetahuan Pentingnya Menjaga Kesehatan Gigi Dan Mulut Dalam Pencegahan Karies (Jurnal Terapi Gigi dan Mulut, 2023)
ABSTRACT Dental and oral health was part of the health of the body and was affecting the health of the body as a whole and cannot be separated. About 80% of Indonesia''s population suffered from tooth decay due to various reasons. High school students (SMA) were generally aged between 15 to 19 years and some were still teenagers. Adolescence was a period of developmental transition between children and adults, with changes in physical, cognitive, and social psychological states. High school students were at the stage of formal operational cognitive development. The study used video modified media about maintaining oral and dental health. With the aim of knowing the level of knowledge of the importance of maintaining dental and oral health in caries prevention through video modifications about the importance of maintaining oral health at MAN 4 Sukabumi. This research used analytic research with a quasi-experimental research design (quasi-experimental). Samples were taken using total sampling with a total of 151 people. Research analysis using Wilcoxon test. The results showed that the average pretest score was 8.38, the posttest average score was 8.92 and the difference was 0.54, with p value 0.000 < 0.05, which means that there was an effect of video modification media on increasing knowledge. It was concluded that there was an increase in the knowledge of class X students at MAN 4 Sukabumi in maintaining the dental health of MAN 4 Sukabumi students. Video media can also be used as a health promotion that can be used to increase knowledge about maintaining dental and oral health.